International Cooperative Testing of the Alkali Digestibility Values for Milled Rice - Juliano, Bienvenido O.; Blakeney, A.B.; Butta, I.; Castillo, D.; Choudhury, N.H.; Iwasaki, T.; Shibuya, N.; Kongseree, N.; Lapis, E.T.; Murty, V. V. S.; Paule, C.M.; Perez, C.M.; et al. (Wiley, 1982)
An international cooperative test involving 11 laboratories showed that comparable results were obtained for alkali digestibility of five milled rice samples by the scoring methods ofLittleet al. andBhattacharyaandSowbhagyaand that 1.7% KOH gave better varietal differentiation of rice starch gelatinization temperature by both methods than 1.1 and 1.4% KOH.